Designing of Restaurant Information System using Rapid Application Development - Wahyu Adi Prabowo; Citra Wiguna (SISFORMA, 2021)
Indonesia is one of the largest culinary attractions in Southeast Asia. The culinary diversity in Indonesia encourages stakeholders to create restaurant businesses with effective and efficient business processes. One of the efforts to make the restaurant business process effective and efficient is to build a restaurant management information system. By using a system, business actors will be able to control and evaluate their business with appropriate reports. For this reason, the purpose of this study is to build a restaurant management information system using the RAD (Rapid Application Development) method, because building this application requires a systematic, structured, and object-oriented process. The RAD method emphasizes a high quality systems, fast development and delivery and low costs development process [1] so that this process requires a serious role from business actors to build a restaurant management information system.   The results of this system design can make it easier for business actors to control the business process from the customer to the kitchen so that the food and beverage ordering process will be served quickly. The GUI restaurant management information system is made interactively so that customers and business actors can easily understand the system. The test results of this system use black-box testing, with the conclusion that the system is successful to run.